LITHOSTRATIGRAPHIC, CONODONT, AND OTHER FAUNAL LINKS BETWEEN LOWER PALEOZOIC STRATA IN NORTHERN AND CENTRAL ALASKA AND NORTHEASTERN RUSSIA - Dumoulin J.A.; Bradley D.C.; Harris A.G.; Repetski J.E.; Gagiev M. (My University, 2002)
Lower Paleozoic platform carbonate strata in northern Alaska (parts of the Arc-tic Alaska, York, and Seward terranes; herein called the North Alaska carbonate plat-form) and central Alaska (Farewell terrane) share distinctive lithologic and faunal fea-tures, and may have formed on a single continental fragment situated between Siberia and Laurentia. Sedimentary successions in northern and central Alaska overlie Late Proterozoic metamorphosed basement; contain Late Proterozoic ooid-rich dolostones, Middle Cambrian outer shelf deposits, and Ordovician, Silurian, and Devonian shal-low-water platform facies, and include fossils of both Siberian and Laurentian biotic provinces. The presence in the Alaskan terranes of Siberian forms not seen in well-studied cratonal margin sequences of western Laurentia implies that the Alaskan rocks were not attached to Laurentia during the early Paleozoic. The Siberian cratonal succession includes Archean basement, Ordovician shal-low-water siliciclastic rocks, and Upper Silurian–Devonian evaporites, none of which have counterparts in the Alaskan successions, and contains only a few of the Lauren-tian conodonts that occur in Alaska. Thus we conclude that the lower Paleozoic plat-form successions of northern and central Alaska were not part of the Siberian craton during their deposition, but may have formed on a crustal fragment rifted away from Siberia during the Late Proterozoic. The Alaskan strata have more similarities to co-eval rocks in some peri-Siberian terranes of northeastern Russia (Kotelny, Chukotka, and Omulevka). Lithologic ties between northern Alaska, the Farewell terrane, and the peri-Siberian terranes diminish after the Middle Devonian, but Siberian afµnities in northern and central Alaskan biotas persist into the late Paleozoic.
Keywords: Paleozoic; Paleozoic; Палеозой